Penggunaan Bahasa Krama Inggil Dalam Penyifatan Allah (Kajian Sosiolinguistik dan Pragmatik dalam Tafsir Al-Qur’an Al-Ibriz Karya Bisri Mustofa) - Anisa Yaumil Maghfiroh; Irma Rumtianing (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2024)
One of the Javanese Tafsir books is the Al-Ibriz Tafsir Book, in which Bisri Mustofa paid attention to the rules for using the Javanese language. This research discusses the nature of Allah in the book Tafsir Al-Ibriz and explains the sociolinguistic and pragmatic studies, which are then linked to the social life of society. This research uses a descriptive-analytical approach with sociolinguistic and pragmatic theories. The results of this research are as follows: in terms of sociolinguistic theory, the use of krama language in the description of Allah in Tafsir Al-Ibriz is a code switch which takes the form of a speech level from Javanese ngoko to Javanese krama. Meanwhile, viewed with pragmatic theory, the use of polite language in this interpretation uses speech act level parameters. Bisri Mustofa uses the language of krama in characterizing Allah because Allah's position is the highest. The relevance of the use of krama inggil language in Tafsir Al-Ibriz to the construction of social values”‹of Javanese society is that Javanese people can apply Javanese krama language as a means of instilling politeness values.